Metallothioneins in Normal and Cancer Cells - Dziegiel, Piotr; Pula, Bartosz; Kobierzycki, Christopher; Stasiolek, Mariusz; Podhorska-Okolow, Marzenna; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book describes the structures of Metallothionein (MT) family members and the cellular functions of MT-1, MT-2 and MT-4 isoforms, as well as provides insights into divergent biological roles of MT-3. The authors explain the involvement of MT molecules in various processes related to carcinogenesis, including an organ-specific presentation of current data concerning their potential impact on the progression of various tumors and the regulatory role of MT family members in the function of the immune system. .
Introduction -- Metallothioneins: structure and functions -- Metallothionein-3 -- The role of metallothioneins in carciogenesis -- Metallothioneins and immune function.
Keywords: Life sciences; Cancer research; Immunology; Cell biology; Life Sciences; Cell Biology; Immunology; Cancer Research; Electronic books